Pengaruh Debt To Equity Ratio, Return On Assets, Price to Book Value Dan Price Earning Ratio Terhadap Pembagian Dividen Pada Perusahaan Manufaktur di Bursa Efek Indonesia - Samosir, Hottua (Pusdikra Publishing, 2024)
The growth and development of the manufacturing industry which has increased in recent years has made investors interested in investing. The purpose of this study was to determine the effect of Debt to Equity Ratio, Return on Assets, Price to Book Value, and Price Earning Ratio on Dividend Distribution in manufacturing companies listed on the Indonesia Stock Exchange. The population used in this research is manufacturing companies listed on the Indonesian Stock Exchange. By using purposive sampling technique, a research sample of 35 companies was obtained. The results of this study show that partially and simultaneously Return on Assets has an effect on dividend distribution in manufacturing companies listed on the Indonesia Stock Exchange.